Debt Management's Contribution to Monetary Policy - Hallowell, Burton C.; Williamson, Kossuth M. (The Review of Economics and Statistics, 1961)
i the proportion of T which is invested in the borrowing country j the proportion of T spent outside the borrowing country p = the proportion of T spent in the lending country (j>p). In the lending country the increase in income will amount to: p.T times the multiplier (allowing for foreign repercussions); (I) while the decline in the balance of payments surplus 3 will be: [T minus p * T plus MPM p T times the multiplier] minus [a secondary increase in export to the borrowing country whose income has gone up]. (2) In the borrowing country, income will rise by: i. T times the foreign trade multiplier (3) while the external deficit will decline by: [T j.T] [MPM.i.T times the foreign trade multiplier]. (4) It is evident from (2) and (4) that the transfer must exceed the foreign exchange requirements of the development program if it is to have a favorable effect on the external position of both nations. This is particularly true for the borrowing country. Provisions may also be made for spacing repayments over periods of inflation. This would reduce the external surplus in the paying country and the external deficit in the receiving country, while damping the inflation in both economies. A policy of countercyclical lending is subject to the same limitation as the use of public work programs in combatting recessions. By the time a foreign investment project gets under way the recession may be over, but work on the project cannot be stopped for the duration of the ensuing boom. (However, the two lags in the transmission of economic fluctuations from developed to underdeveloped countries would reduce some of this inflexibility.) This is another reason why the responsibility for such a policy must rest with a public body. Some useful investment projects can no doubt be found which are flexible in nature and adaptable to cyclical needs. The amount of the transfer should in any case exceed the immediate costs of these projects. Furthermore, the subject under discussion would not constitute the entire lending program, but only a small part of it. International transfers should be geared to development requirements and not to cyclical fluctuations. Nor can cycle policy be used to justify foreign lending. But inasmuch as lending programs are conducted to foster economic development, there is no reason why they should not be used in part to combat economic fluctuations and external imbalances. ing 1947-1958: Y = -0.225 + o.oo63 X 4o.II6; r= o.682. 'These adjustments are limited to the income effects and should be supplemented by changes in the terms of trade.